Factor Model for Stress-testing with a Contingent Claims Model of the Chilean Banking System - Gray, Dale (IMF Working Papers; Working Paper ;, 2008)
This paper derives risk indicators for the major Chilean banks based on contingent claims analysis, an extension of Black-Scholes-Merton option-pricing theory. These risk indicators are clearly tied to macroeconomic and financial developments in Chile and outside, but bank responses are highly heterogeneous. To reduce the number of variables linked to the banks' risk to a tractable number, we apply principal component analysis. Vector autoregressions of risk indicators with the most significant factors show strong ties from financial markets and regional developments. Impulse response functions from these factors are derived, which allow for scenario testing. The scenarios derived in the paper illustrate how the magnitude and persistence of responses of bank credit risk can vary across banks in the system.